PENGARUH TINGKAT PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI MASYARAKAT DI KABUPATEN BOLAANG MONGONDOW UTARA - Dewanti Tegila; Rosman Ilato; Abdulrahim Maruwae; Radia Hafid; Fitri Hadi Yulia Akib (Oikos Nomos, 2023)
This descriptive quantitative research employs multiple linear analysis techniques and calculations using panel data. The type of data used in this study is secondary data obtained from the central bureau of statistis with a cross section of 1sub-districts in North Sulawesi Province and a time series of 12 years. The data analysis used is panel data analysis with a fixed effect modell. Data are processed using eviewss 8 tool.It can be concluded that there are 3 types of statistical tests, namely the goodness of it test (R2), the simultaneous F test (F test), and the statistic t test, all of which are not significan or in other words, have a negative impact. The classical assumptions test used is the autocorrelation test, the heteroscedasticity test has a negative effect and the multicollinearity test has a positive effect.The study’s finding’s demonstrated that both the level of education (X) and the economic growth (Y) had a negative an not significant effect or North Bolaang Mongondow Regency in 2011-2022.